2000
DOI: 10.1016/s0168-1591(99)00083-0
|View full text |Cite
|
Sign up to set email alerts
|

Suckling and allosuckling in river buffalo calves and its relation with weight gain

Abstract: The aim of the present study was to investigate if river buffalo calves (Bubalus bubalis) have equal access to all cows and if milk is thus equally available to all of them. We recorded suckling/allosuckling behaviour and weight gain (WG) of 29 calves (14 males and 15 females), with special consideration to their sex, birth order (B0) and age. Cows' nursing behaviour and milk production (MP) were also considered. While males tended to be bom earlier than females during this study, this was not the trend in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 7 publications
2
15
0
3
Order By: Relevance
“…In reindeer, rapid milk ejection is required since calves suckle frequently and for short durations (White and Luick, 1984). Therefore, we assumed that milk transfer occurred, and a similar assumption was made in other studies (Drábková et al, 2008;Gauthier and Barrette, 1985;Paranhos da Costa et al, 2000;Pélabon et al, 1998;Zapata et al, 2009).…”
Section: Behavioural Observationsmentioning
confidence: 92%
See 3 more Smart Citations
“…In reindeer, rapid milk ejection is required since calves suckle frequently and for short durations (White and Luick, 1984). Therefore, we assumed that milk transfer occurred, and a similar assumption was made in other studies (Drábková et al, 2008;Gauthier and Barrette, 1985;Paranhos da Costa et al, 2000;Pélabon et al, 1998;Zapata et al, 2009).…”
Section: Behavioural Observationsmentioning
confidence: 92%
“…Because age of calf has been shown to increase the occurrence of allosuckling in calves of camels (Brandlová et al, 2013), fallow deer (Ekvall, 1998) and red deer (Landete-Castillejos et al, 2000), we controlled for this effect by including age of calf (in days) as a covariate in our model. Birth mass was added as a covariate, since calves of cattle cows (Víchová and Bartoš, 2005) and river buffalo (Paranhos da Costa et al, 2000) with low birth mass performed more allosuckling. Sex of calf was added as a covariate, since male river buffalo calves spent more time allosuckling than female calves (Paranhos da Costa et al, 2000), and female cattle calves had a higher incidence of allosuckling than male calves (Víchová and Bartoš, 2005).…”
Section: Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Paranhos da Costa et al (2000) reported that sex of calf influenced the number of feedings and total duration of suckling. Males had a mean of 2.60±0.03 feeds per day with a total duration of 25.05±1.37 min/day, while females averaged 2.12±0.04 and 21.51±1.55 feeds and min/day respectively.…”
Section: Discussionmentioning
confidence: 99%